Relação entre níveis de atividade física, índices antropométricos e função pulmonar de escolares da rede pública de Porto Alegre/RS - Pazini, Fernanda (2018)
Introduction: Asthma is a chronic respiratory disease of high prevalence in the child population. Its diagnosis and correct treatment are essential so that the patient does not move away from their routine activities. For this population, guided physical activity can help decrease the symptoms of the disease, improve cardiorespiratory fitness, reduce fat levels and increase muscle mass, decrease school absenteeism levels, and raise quality of life scores. Objective: To evaluate and correlate levels of physical activity with the pulmonary function of children diagnosed with asthma at school. Methods: This study was accomplished out in two phases, in schoolchildren from Porto Alegre / RS, from 8 to 16 years old. In the phase I (transversal) the sample was characterized, being applied to the responsible ones of the students a questionnaire of diagnosis of the asthma, following the standards of the international study "The International Study of Asthma and Allergies in Childhood - ISAAC". In phase II (casecontrol) after the characterization and identification of the asthma and control groups (healthy) the anthropometry, physical activity levels and pulmonary function (spirometry) were evaluated. For the purposes of statistical analysis, the descriptive and categorical variables were presented by absolute and relative frequencies. The descriptions of the continuous variables were presented through mean and standard deviation (SD). For comparison between groups, the values were analyzed using the chi-square test and the Pearson test correlations, with a significance value at p<0.05. Results: A total of 605 students participated in the study, of which 290 were children with clinical diagnosis of asthma and 315 were classified as controls. Of the total, 280 (47.3%) male children, with a mean age of 11.0±2.3 years. The categorical spirometric values showed differences in the classifications of airway obstruction levels between asthma and control groups (p 0.005), and the response to bronchodilator use >12% for FEV1/FVC (p=0.023). The values of pulmonary function, anthropometric measurements and physical activity levels were significantly different for spirometric values, showing differences in pre-FEV1 and FEV1/FVC, p=0.008 and p<0.001, respectively) (FEV1/FVC, p=0.003), for the anthropometric values, only the RCE variable presented a modest difference (p=0.048), not being different for the means of physical activity or risk of physical inactivity idle time in front of screens. In the correlation evaluation, these results show a low correlation between the time spent in physical activities for the FEV1 variables [R2=0.13; p=0.012] and FVC [R2 0.12; p=0.035]) for the asthma group, at the time after bronchodilator use. Conclusion: The study shows differences in spirometric volumes, especially after bronchodilator application, indicating obstructive disorders in asthmatic children. At the same time, it shows a low relation between anthropometric values and levels of physical activity with the pulmonary function of school children.